Analisis Simbol-Komunikasi Budaya dalam Arsitektur Masjid Lautze 2 Melalui Teori Semiotika Charles Sanders Peirce - Aras, Taufik Setyadi; Hifajar, Wahyu; Kancana, Selmabelle Garluisya Simbar; Sya'ban, Feni Khairunnisa; Hafiz, Nabil Dwika (Jurnal Artefak, 2025)
The research aims to examine and describe how the symbols contained in the architecture of the Lautze 2 Mosque function as a medium of cultural communication. Using Peirce's semiotics approach, this study analyzes the visual and structural elements of mosques that reflect the cultural and religious values of the community. The mosque is unique in that it combines two different cultural traditions in one sacred building. This phenomenon raises questions about how communication and cultural symbols are integrated into the architecture of mosques and what their implications are for the identity of the community. The research uses a qualitative method with semiotic analysis, where data is collected through direct observation and literature study. The results of the analysis show that the existing symbols, such as building shapes, ornaments, and colors, not only serve as aesthetic elements but also convey deep moral and spiritual messages. The research identified three categories of signs according to Peirce: icons, indexes, and symbols, each of which has an important role in establishing the architectural meaning of mosques. The elements analyzed include the front façade, pulpit, calligraphy, and mosque partition ornaments. The results of the study show that 1) Mosque architecture integrates Islamic and Chinese cultural symbols, creating a visual narrative of intercultural harmony and inclusivity, 2) The combination of Islamic and Chinese elements presents a unique cultural synthesis, and 3) The existence of the Lautze 2 Mosque affirms the identity of Chinese Muslims while conveying the message of intercultural harmony in Indonesia.